Pemahaman Nilai-nilai Pendidikan Karakter Islami dalam cerita Anak oleh Guru Madrasah Ibtidaiyah (MI) dan SD se Kecamatan Sukodadi: Tinjaun Pragmatik Reseptif - Ernaningsih Ernaningsih; Luluk Faridah (Universitas Islam Darul 'Ulum Lamongan, 2020)
This research focuses on (1) how to understand the values of Islamic character education contained in children's stories by SD/MI teachers in the Sukodadi sub-district, (2) how to contextualize the values of Islamic character education contained in children's stories to improve religious learning models . The aims of this research are to describe and explain: (1) the understanding of Islamic character education values contained in children's stories by SD/MI teachers in the Sukodadi sub-district, and (2) the contextualization of Islamic character education values contained in children's stories as improvement of religious learning models. The method used in this study is descriptive qualitative with a receptive pragmatic approach. The data in this study are in the form of data on (1) understanding of Islamic character education values contained in children's stories, and (2) contextualization of character education values contained in stories as a model of Islamic learning. Sources of data obtained from documentation and interviews. The data collection technique is done by documentation and interviews. Data analysis techniques using interactive techniques. Data validation uses triangulation, both theory, data, and method triangulation. The results of the research findings can be described as including: (1) Understanding the value of Islamic character education in children's stories, Faithful morality, gratitude, Devotion to both parents and teachers, Healthy and clean, Mutual Cooperation and Virtuous Morals not arrogant, (2) contextualization of the values of Islamic character education contained in children's stories as an improvement in Islamic religious learning models.